Fundamentals of behavioral statistics. - Runyon, Richard P.; Runyon, Richard P. (New York : McGraw-Hill, 1996)
A book on behavioral statistics.
Rev. ed. of: Fundamentals of behavioral statistics / Richard P. Runyon. 7th ed. c1991.
Includes bibliographical references (p. 712-714) and index.
rua 03/03/15
Loans
Keywords: Social sciences -- Statistical methods; Statistics; Psychometrics; Statistics